(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Maternal nutrition is a cornerstone of a healthy pregnancy, directly influencing fetal development and reducing complications. In regions like Sindh, Pakistan, where malnutrition is prevalent, understanding the nutritional awareness of pregnant women is critical for designing effective public health interventions. Objectives: This study aimed to assess the nutritional knowledge, attitudes, and dietary practices of pregnant women attending antenatal clinics at Liaquat University Hospital, Hyderabad. Methods: A descriptive cross-sectional study was conducted using a structured questionnaire administered to pregnant women at the antenatal clinics. Data were collected on dietary habits, knowledge of essential nutrients, attitudes towards nutrition, and sources of information. The data were analyzed using descriptive statistics to identify key trends and gaps. Results: A significant disparity was found between attitude and practice. While all respondents (100%) agreed a healthy diet is beneficial and 76.7% believed it reduces complications, dietary practices were suboptimal. A majority (62.0%) did not consume breakfast daily, and daily intake of fruits, vegetables, and milk products was low (16.0% and 14.0%, respectively). While 54.0% were taking iron and folic acid, adherence was a challenge. Knowledge of specific nutrients was varied, and women relied equally on healthcare providers (42.0%) and family/friends (42.0%) for information. Conclusion: Pregnant women in this cohort possess a positive attitude towards nutrition but lack the practical knowledge and dietary habits to support a healthy pregnancy. There is an urgent need for targeted, accessible educational interventions to bridge this gap and improve maternal and fetal health outcomes.